Beta-lactamase database (BLDB) – structure and function. (1st January 2017) - Naas, Thierry; Oueslati, Saoussen; Bonnin, Rémy A.; Dabos, Maria Laura; Zavala, Agustin; Dortet, Laurent; Retailleau, Pascal; Iorga, Bogdan I.
Abstract: Beta-Lactamase Database (BLDB) is a comprehensive, manually curated public resource providing up-to-date structural and functional information focused on this superfamily of enzymes with a great impact on antibiotic resistance. All the enzymes reported and characterised in the literature are presented according to the class (A, B, C and D), family and subfamily to which they belong. All three-dimensional structures of β-lactamases present in the Protein Data Bank are also shown. The characterisation of representative mutants and hydrolytic profiles (kinetics) completes the picture and altogether these four elements constitute the essential foundation for a better understanding of the structure-function relationship within this enzymes family. BLDB can be queried using different protein- and nucleotide-based BLAST searches, which represents a key feature of particular importance in the context of the surveillance of the evolution of the antibiotic resistance. BLDB is available online at http://bldb.eu without any registration and supports all modern browsers.